KUALITAS SANITASI LINGKUNGAN TEMPAT TINGGAL MASYARAKAT DI KELURAHAN TAIPA KOTA PALU - Anita Pratiwi; Andi Iin Nindy Karlinda Kadir; Awwalini Maghfirah Salim; Darasita Zahra Dayanun; M.Marjan; Alricha (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2025)
Proper environmental sanitation is an essential component in ensuring a healthy and safe quality of life for communities. Taipa Subdistrict in Palu City has experienced significant growth in infrastructure and population; however, challenges remain in the areas of sanitation and household waste management. This study aims to evaluate the environmental sanitation conditions in Taipa and their impact on public health. The research employed a descriptive quantitative method using a survey approach conducted on 512 households through field observations, interviews, and questionnaires. The results revealed that most residents rely on bore wells as their main sources of clean water and drinking water, while the use of piped water (PDAM) remains limited. Nearly all households have access to healthy latrines and use septic tanks for fecal waste disposal. However, the management of used cooking oil and the practice of open burning of waste remain environmental concerns that require attention. The majority of houses have floors and walls that meet environmental health standards. These findings indicate that although basic sanitation has been categorized as fairly adequate, efforts in public education and improvement of waste management systems are still needed to ensure sustainable environmental health in the community.